2014
DOI: 10.1038/srep06185
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of gut microbiota reveals multiple bacterial communities with distinct characteristics

Abstract: We analyzed bacterial communities of six distinct gut sites (the food bolus and mucus layer of the proximal small intestine, cecum and distal large intestine), using wild folivorous flying squirrels. We found significant spatial heterogeneity in composition, diversity, and species abundance distributions (SADs) of gut microbiota, corresponding to physicochemical conditions. High diversity was detected in the mucus layer of small intestine and the food bolus of cecum, followed by the food bolus of large intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 56 publications
10
28
0
Order By: Relevance
“…Despite these limitations, our findings strengthen previous assertions that the high‐fiber diet of Abert's squirrels has shaped the evolution of the GI tract of this species (Murphy & Linhart, ). Moreover, our data corroborate previous research documenting distinct microbial communities in the upper and lower GI tract (Gu et al, ; Kohl, Dearing, et al, ; Lu et al, ; Suzuki & Nachman, ). Although few studies have compared microbial communities along the length of the GI tract in different species, our findings align with previous research suggesting the microbiota of the lower GI tract may be more divergent between species than microbial communities inhabiting the upper GI tract (Kohl, Dearing, et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite these limitations, our findings strengthen previous assertions that the high‐fiber diet of Abert's squirrels has shaped the evolution of the GI tract of this species (Murphy & Linhart, ). Moreover, our data corroborate previous research documenting distinct microbial communities in the upper and lower GI tract (Gu et al, ; Kohl, Dearing, et al, ; Lu et al, ; Suzuki & Nachman, ). Although few studies have compared microbial communities along the length of the GI tract in different species, our findings align with previous research suggesting the microbiota of the lower GI tract may be more divergent between species than microbial communities inhabiting the upper GI tract (Kohl, Dearing, et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, most alpha ‐diversity measurements were higher in samples from the lower GI tract than the upper GI tract. These results parallel findings in several other rodent species where samples from the upper and lower GI tract are clearly delineated by community membership, and lower GI samples typically have higher diversity (Gu et al, ; Kohl, Dearing, et al, ; Lu et al, ; Suzuki & Nachman, ). Consistent with lower overall diversity in the upper GI tract, the core microbiota of upper GI samples were comprised of few species, which also indicates high individual heterogeneity in this community.…”
Section: Discussionsupporting
confidence: 79%
“…Within the posterior gastrointestinal tract, the ileum and rectum harbored more complex microbial assemblages (e.g., high alpha diversity). Previous studies have demonstrated that the neutral pH maintained within this region of the digestive tract offers a more conducive internal environment for the maintenance of larger microbial assemblages than those found in highly acidic stomachs (Lu et al, ). The length of the gastrointestinal tract chambers increases significantly following this compartmentalization process.…”
Section: Discussionmentioning
confidence: 99%
“…Divergence between the mucosal and digesta - associated colonic communities has been observed in several mammals including humans 28 , macaques 29 , mice 30 , cows 31 , and flying squirrels 32 . More specifically, human colon biopsy and swab samples have revealed a distinct mucosal community enriched in Actinobacteria and Proteobacteria compared to the lumen community 33 .…”
Section: Microbial Composition Of the Gutmentioning
confidence: 99%